Reconceptualising Conservation: Towards Updating a Section of the District Plan for Driftsands - Winkler, Alexandra (School of Architecture, Planning and Geomatics, 2023)
With the threat of Climate change combined with rapid urban expansion, the threat to natural systems is increasingly dire (Korten, 2022). Historically, the entities of nature and people have long been pitted against each other within mainstream conservation (Kiwango & Mabele, 2022). Conservation has often been seen as a tool for the elite to control land and land use, often at the expense of marginalised communities (Kepe & Mollett, 2018). However, with the increasing threat to protected areas, there has been an emergence of alternative conservation strategies, including convivial and decolonial conservation. The dissertation will utilise the Driftsands Area as a case study to consider and investigate alternative conservation methods with a particular focus on water management. The site has seen the encroachment of people into the Nature Reserve, which has degraded the space leading to the initiation of the process of de-proclamation of the site (WCG, 2021). The needs and priories of people and nature seem in direct conflict, where setters are in need of land to settle however, this is threatening the ecosystems in the space and also posing a threat to people as some setters have moved into the flood zone (WCG, 2021). There is thus a need to consider this site as a case study to rethinking conservation. The site provides an opportunity for planners to reconsider alternative methods of conservation. Therefore, the aim of the study is to introduce a layer of the sub-district plan that includes concepts that allow for people and nature to be protected together within the site and gives special consideration to protecting the valuable ecosystem systems in the area, notably the water systems (Kuils River and Wetlands) in this space. The case study of Driftsands will be supported by desktop research, a site visit and expert interviewees in the space to introduce and develop alternative methods to conserve the site. The study showed that there are alternative methods to protect nature and people; importantly, in Driftsands, the flood zone can be introduced as a promoted rather than a protected area, namely by introducing concepts such as a multi-use urban park and identifying areas for relocation of the settlements at risk in the flood zone. The layer of the sub-district plan for Driftsands can serve as a base late for future plans. This research can contribute to the various case studies and studies around alternative conservation methods and aim to add to the various examples of sites and cases that utilised the imminent de-proclamation as an opportunity to rethink and reconceptualise urban conservation.